An integrated vision-based architecture for home security system - See, J.; Sze-Wei Lee, S.-W. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2007)
Automated security systems are a useful addition to today's home where safety is an important issue. Vision-based security systems have the advantage of being easy to set up, inexpensive and non-obtrusive. This paper proposes an integrated dual-level vision-based home security system, which consists of two subsystems - a face recognition module and a motion detection module. The primary face recognition module functions as a user authentication device. On an event of a failure in the primary system, the secondary motion detection module acts as a reliable backup to detect human-related motions within certain locations inside the home. Novel algorithms have been proposed for both subsystems. Several experiments and field tests conducted have shown good performance and feasible implementation in both subsystems.